Event studies : theory and management for planned events - Getz, Donald, 1949-; Page, Stephen, 1963- (London ; New York : Routledge/Taylor & Francis Group, 2024)
Fully updated and revised in its fifth edition, Event Studies remains the most comprehensive book devoted to developing knowledge and theory about event management and event tourism, focusing on the study of events, the event experience, and meanings associated with them. International in scope and embellished with useful figures and tables throughout, the authors carefully examine current forces, trends, and issues, including impacts of the pandemic. All the major types of planned events are profiled, with emphasis on their forms, functions, experiential dimensions, meanings, and values. This book’s framework encompasses antecedents, planning and design, outcomes and impacts, and the various patterns and processes that influence the events sector, including policy.
Páté, zásadně aktualizované vydání publikace představuje nejucelenější teoretický a praktický přehled problematiky plánovaných akcí a event managementu. Autoři systematicky rozvíjejí teorii studia událostí, zaměřují se na povahu a typologii eventů, zážitek účastníků, významy a hodnoty, které jsou s akcemi spojeny, i na jejich společenské, ekonomické a kulturní dopady. Kniha podrobně analyzuje celý proces vzniku a realizace akcí – od východisek, plánování a designu přes řízení a politické souvislosti až po hodnocení výsledků a dopadů, včetně reflexe aktuálních trendů a důsledků pandemie.
Název z titulní obrazovky
Obsahuje bibliografické odkazy a rejstřík
Způsob přístupu: Internet
Keywords: event management; event marketing; plánování scénářů; zážitková turistika; kolektivní monografie; případové studie; event management; event marketing; scenario planning; experience tourism; collective monographs; case studies